Combinatorial liposomal peptide vaccine induces IgA and confers protection against influenza virus and bacterial super‐infection. Issue 9 (10th September 2021) - Zaman, Mehfuz; Huber, Victor C; Heiden, Dustin L; DeHaan, Katerina N; Chandra, Sanyogita; Erickson, Demi; Ozberk, Victoria; Pandey, Manisha; Bailly, Benjamin; Martin, Gael; Langshaw, Emma L; Zaid, Ali; et al.
Abstract: Objectives: The upper respiratory tract is the major entry site for Streptococcus pyogenes and influenza virus. Vaccine strategies that activate mucosal immunity could significantly reduce morbidity and mortality because of these pathogens. The severity of influenza is significantly greater if a streptococcal infection occurs during the viraemic period and generally viral infections complicated by a subsequent bacterial infection are known as super‐infections. We describe an innovative vaccine strategy against influenza virus: S . pyogenes super‐infection. Moreover, we provide the first description of a liposomal multi‐pathogen‐based platform that enables the incorporation of both viral and bacterial antigens into a vaccine and constitutes a transformative development. Methods: Specifically, we have explored a vaccination strategy with biocompatible liposomes that express conserved streptococcal and influenza A virus B‐cell epitopes on their surface and contain encapsulated diphtheria toxoid as a source of T‐cell help. The vaccine is adjuvanted by inclusion of the synthetic analogue of monophosphoryl lipid A, 3D‐PHAD. Results: We observe that this vaccine construct induces an Immunoglobulin A (IgA) response in both mice and ferrets. Vaccination reduces viral load in ferrets from influenza challenge and protects mice from both pathogens. Notably, vaccination significantly reduces both mortality and morbidity associated with a super‐infection. Conclusion: The vaccine design is modular and could be adapted to include B‐cell epitopes from other mucosal pathogens where an IgA response is required for protection. Abstract : In this study, we report on the potential of a modular multi‐pathogen mucosal vaccine. We found that this vaccine construct induces an Immunoglobulin A (IgA) response in both mice and ferrets. Vaccination reduces viral load in ferrets from influenza challenge and protects mice from influenza virus: S . pyogenes super‐infection.